Pengaruh Manajemen Hubungan Masyarakat Terhadap Kualitas Pelayanan Akademik SMAN Darussholah Singojuruh Banyuwangi - Siti Aimah; Ulfa Dwi Yanti (Institut Agama Islam Darussalam Blokagung, 2020)
The purpose of this study was to find out how the application of public relations management at Darussholah Singojuruh Banyuwangi Senior High School of State. Second, how is the quality of academic services at Darussholah Singojuruh Banyuwangi Senior High School of State. Third, is there any influence of public relations management on the quality of academic services at Darussholah Singojuruh Banyuwangi Senior High School of State. Fourth, how much influence does public relations management have on the quality of academic services at Darussholah Singojuruh Banyuwangi Senior High School of State. The data collection methods used in this study are questionnaire, observation, documentation. As for the data validity test using the product moment formula, to look for data reliability using the Cornbach, Alpha formula. Then for hypothesis testing using the T test and F test, for the normality test using the Kolmogorov-Smirnov formula. In the analysis of data using Simple Linear Regression analysis. The results of this study indicate there is an influence of public relations management on the academic service quality of Darussholah Singojuruh Banyuwangi Senior High School of State by 74.4% while the remaining 25.6% is influenced by other variables not examined, which means the effect of public relations management on the academic quality of Darussholah Singojuruh Banyuwangi Senior High School of State is good.